Das saudades que se tem: a representação paterna na escrita autobiográfica de Bartolomeu Campos de Queirós - Silva, Carla Damas (2016)
In our work, we analyze some works of Bartolomeu Campos de Queirós that compose the “autobiographical cycle”, especially those ones that bring the image of father’s absence/presence, the relationship between life and writing, as well as the father’s figurations and his intermediates and substitutes. We especially investigated the aspect of repetition about how the family relations are articulated, highlighting those ones that happen between father and son and that appear in these texts. This problematic interested us as a research object, a priori, because the works of Bartholomeu Campos de Queirós are an exponent of literature for children field, as far as they show that the childhood is not always “colorful”, happy and perfect as several productions supposedly made “for children” seek to have us believe. In addition, the selected texts that have an autobiographical characteristic and put the issue of child suffering because of the father’s absence are configured as a very rich corpus for studies related to the relation between life/work and investigations in the dialogue between Literature and Psychoanalysis. These aspects will permit us to understand why the pain of missing father be repetitive and insistent in these books. Thus, we problematize, by the selected works for this study, the concept of literature for children and young people and the notion of literary reading. We also analyzed in the “statements” given by the author the relationship between life and writing and we investigated, based on psychoanalytic studies, the literary writing as a possibility of both unconscious development of memory marked by the father’s absence – remedy – as of a perpetuation of this same conflict – poison. Furthermore, we analyzed how the relationship between son and father are processed considering the mother’s absence, since the works that have this person’s presence, she seems to mediate such relationships in a certain way.